Simplify Exponents and Radicals Questions

Review and use the the rules for radicals and exponents to simplify exponents and radical expressions; questions with detailed solutions (lower part of page) and explanations are presented. Try not to use the calculator to simplify numerical expressions except to check your answers. More questions on how to simplify radical expressions are included n this website.

Simplify Numerical Expressions with Exponents

Question 1

Evaluate the following expressions:
  1.   3 2
  2.   - 3 4
  3.   (- 3) 4
  4.   12 0
  5.   0 20
  6.   0 - 4
  7.   (-1) 7
  8.   (-1) 4
  9.   (-1) - 3
  10.   (- 2 / 3) -2
  11.   (- 2) -2 / 4 -2
  12.   - 3 -3 + (- 2) -2
  13.   x 4 for x = - 2
  14.   - x 2 for x = - 3
  15.   - x 5 for x = - 2
  16.   x 4 for x = - 2 / 3
  17.   - x -2 for x = - 1 / 2
  18.   - x 5 for x = - 1 / 3


Simplify Numerical Expressions with Radicals and rational exponents

Question 2

Evaluate the following expressions:
  1.   √(64)
  2.   ∛(-8)
  3.   4 3/2
  4.   8 2/3
  5.   0.0001 3/4
  6.   16 - 3/4
  7.   √2 √8
  8.   ∛2 ∛(32)
  9.   √2 / √8
  10.   ∛(-16) / ∛2
  11.   - 2 (6√8) (56√8)
  12.   - 4 ∛(375) / (2∛3)


Simplify Algebraic Expressions with Exponents

Question 3

Simplify the following expressions:
  1.   x 2 x 5
  2.   y 4 / y 2
  3.   (x 2) -2

  4. \large {3(\dfrac{1}{2} x^4)(\dfrac{1}{3} x^3) }

  5. \large {(2 x)^4(\dfrac{1}{4} x^{-3}) }

  6. \large { \dfrac{(3x)^2(-2x)^3}{(2x)^2} }

  7. \large { \dfrac{(4x)^2(100 x)^0}{(3x)^2} }
  8.   (- 2 x2 y -3)3
  9.   (3 x2 y3) (2 x5 y - 2)
  10.   (- 2 x2 y3 z4) ( - 4 x3 y z - 8) ( 5 x y2 z2)

  11. \large { (-2xy^2)^2 \left (\dfrac{x^6}{(2x)^2} \right)^3 }

  12. \large { \left (\dfrac{4 x^6 y^3}{-8x^3y^{-2}} \right) }

  13. \large { \left (\dfrac{- 4 x^3 y^2}{3 x^3 y^3} \right) \left (\dfrac{3 x^2 y^5}{-6x^3y^2} \right) }

  14. \large { \dfrac{1}{6}(x^2 y z^3)\left (\dfrac{4 x^2 y^3}{3 x^2 y^{-3}z^2} \right) \left (\dfrac{3 x^2 y^5 z}{-x^3 y^2 z^3} \right) }

  15. \large { (4 x^{2/3})(-8x^{1/2}) }

  16. \large { (4 x)^{3/2}(9x)^{1/2} }

  17. \large { (- 27 x^{3/2})^{1/3} }

  18. \large {\left (\dfrac{-8x^3}{y^{-6}} \right)^{2/3} }

  19. \large { x^{5/3} x^{1/6} x ^{-11/6} }


Simplify Algebraic Expressions with Radicals

Question 4


  1. \large { \sqrt{x^2} }

  2. \large { \sqrt[4]{16x^4} }

  3. \large { \sqrt{(2x - 1)^2} }

  4. \large { \sqrt[3]{-27x^3} }

  5. \large { \sqrt[3]{8 x^6 y^3} }

  6. \large { \sqrt{x^3} \sqrt{x^2} }

  7. \large { \sqrt[3]{\left (\dfrac{-8x^6}{y^{-3}} \right)} y}

  8. \large { \dfrac{ \sqrt[5]{64x^9 y^7}}{ \sqrt[5]{2 x^4 y^2}} }

  9. \large { (4\sqrt[8]{b^2})( 5\sqrt[8]{b^3})( \sqrt[8]{b^3}) }


Solutions to the Above Questions

Question 1

Evaluate the following expressions:
  1.   3 2 = 3 3 = 9
  2.   - 3 4 = - (3 3 3 3 ) = - 81
  3.   (- 3) 4 = - 3 - 3 - 3 - 3 ) = 81
  4.   12 0 = 1
  5.   0 20 = 0
  6.   0 - 4 = 1 / 0 4 = 1 / 0 : undefined because division by zero is not allowed in maths.
  7.   (-1) 7 = - 1
  8.   (-1) 4 = 1
  9.   (-1) - 3 = 1 / (-1) 3 = 1 / (- 1) = - 1
  10.   (- 2 / 3) -2 = (- 3 / 2) 2 = (-1) 2 ( 3 / 2) 2 = 9 / 4
  11.   (- 2) -2 / 4 -2 = 4 2 / (- 2) 2 = 16 / 4 = 4
  12.   - 3 -3 + (- 2) -2 = - 1 / 3 3 + 1 / (- 2) 2 = - 1 / 27 + 1 / 4 = 23 / 108
  13.   x 4 for x = - 2
    x 4 = (-2) 4 = 16
  14.   - x 2 for x = - 3
    - x 2 = - (-3) 2 = - 9
  15.   - x 5 for x = - 2
    - x 5 = -( - 2) 5 = 32
  16.   x4 for x = - 2 / 3
    (- 2 / 3) 4 = (-2) 4 / (3) 4 = 16 / 81
  17.   - x -2 for x = - 1 / 2
    - x -2 = - (- 1 / 2) -2 = - ( - 1) -2 ( 1 / 2) -2
    = - (1) (2 / 1) 2 = - 4 / 1 = - 4
  18.   - x 5 for x = - 1 / 3
    - x 5 = - ( - 1 / 3) 5 - ( - 1) 5( 1 / 3)5
    = - (-1) (1 / 243) = 1 / 243


Question 2

Evaluate the following expressions:
  1.   √(64) = √(8 2) = 8
  2.   ∛(-8) = ∛((-2)3) = - 2
  3.   4 3/2 = (√4) 3 = 2 3 = 8
  4.   8 2/3 = (∛(8)) 2 = 2 2 = 4
  5.   0.0001 3/4 = ( 4√(0.0001) ) 3
    = ( 4√(1/10000) ) 3 = ( 4√(1/104) )3
    = ( 1 / 10 ) 3 = 1 / 10 3 = 0.001
  6.   16 - 3/4 = 1 / 16 3/4 = 1 / ( 4√(16)) 3
    = 1 / 2 3 = 1 / 8
  7.   √2 √8 = √(2 8) = √(16) = 4
  8.   ∛2 ∛(32) = ∛(2 32) = ∛(64) = 4
  9.   √2 / √8 = √(2 / 8) = √(1 / 4) = 1 / 2
  10.   ∛(-16) / ∛2 = ∛(-16/2) = ∛(- 8) = - 2
  11.   - 2 ( 6√8) (5 6√8) = (- 2 5) 6√(8 8)
    = - 10 6√(64) = - 10 6√(26) = -10(2) = - 20
  12.   - 4 ∛(375) / (2∛3) = (- 4 / 2) ∛ (375 / 3) = - 2 ∛ (375 / 3)
    = - 2 ∛ (125) = - 2 5 = - 10


Question 3

Simplify the following expressions:
  1.   x 2 x 5 = x 2 + 5 = x7
  2.   y 4 / y 2 = y 4 - 2 = y 2
  3.   (x 2) -2 = (x 2 (-2)) = x - 4 = 1 / x 4

  4. \large {3(\dfrac{1}{2} x^4)(\dfrac{1}{3} x^3) = (3 \times \dfrac{1}{2} \times \dfrac{1}{3} ) x^{4 + 3} = \dfrac{1}{2} x^7}

  5. \large {(2 x)^4(\dfrac{1}{4} x^{-3}) = 2^4 x^4 (\dfrac{1}{4} x^{-3}) \\\\ = (2^4 \times \dfrac{1}{4}) x^{4-3} = 4 x}

  6. \large { \dfrac{(3x)^2(-2x)^3}{(2x)^2} = \dfrac{3^2 x^2 (-2)^3 x^3}{2^2 x^2} \\\\ = \dfrac{3^2 (-2)^3}{2^2} \dfrac{x^3}{x^2} = - 18 x }

  7. \large { \dfrac{(4x)^2(100 x)^0}{(3x)^2} = \dfrac{4^2 x^2 \times 1}{3^2 x^2} = 16/9 }
  8.   (- 2 x 2 y -3) 3 = (- 2) 3 (x 2) 3 (y -3) 3 = - 8 x 6 y -9 = - 8 x 6 / y 9
  9.   (3 x2 y 3) (2 x 5 y - 2) = (3 2)(x 2 x 5)(y 3 y - 2) = 6 x 2 + 5 y 3 - 2 = 6 x 7 y
  10.   (- 2 x 2 y 3 z 4) ( - 4 x 3 y z - 8) ( 5 x y 2 z 2) = (-2 (-4) 5)(x 2 x 3 x)(y 3 y y 2)(z 4 z -8 z 2)
    = 40 x 2 + 3 + 1 y 3 + 1 + 2 z 4 - 8 + 2 = 40 x 6 y 6 z - 2 = 40 x 6 y 6 / z 2

  11. \large { (-2xy^2)^2 \left (\dfrac{x^6}{(2x)^2} \right)^3 = (-2)^2 x^2 y^4 \left (\dfrac{x^{18}}{(2x)^6} \right) = \dfrac{4x^2 y^4x^{18}}{2^6 x^6}} \\\\ \large { = \dfrac{4}{2^6} \dfrac{x^{2+18}y^4}{x^6} = \dfrac{1}{16} {x^{14} y^4} }

  12. \large { \left (\dfrac{4 x^6 y^3}{-8x^3y^{-2}} \right) = \dfrac{4}{-8} \; \dfrac{x^6 y^3}{x^3y^{-2}} = -\dfrac{1}{2} x^{6-3} y^{3-(-2)} = -\dfrac{1}{2} x^3 y^5 }

  13. \large { \left (\dfrac{- 4 x^3 y^2}{3 x^3 y^3} \right) \left (\dfrac{3 x^2 y^5}{-6x^3y^2} \right) = \dfrac{(- 4 \times 3)}{(3 \times (-6))} \dfrac{(x^3 y^2)(x^2 y^5)}{(x^3 y^3)(x^3y^2)} }\\\\\\ \large { = \dfrac{2}{3} \dfrac{x^5 y^7}{x^6 y^5} = \dfrac{2}{3} x^{5-6} y^{7-5}= \dfrac{2}{3} \dfrac{y^2}{x} }

  14. \large { \dfrac{1}{6}(x^2 y z^3)\left (\dfrac{4 x^2 y^3}{3 x^2 y^{-3}z^2} \right) \left (\dfrac{3 x^2 y^5 z}{-x^3 y^2 z^3} \right) = \dfrac{1 \times 4 \times 3}{6 \times 3 \times (-1)} \dfrac{(x^2 y z^3)(x^2 y^3)(x^2 y^5 z)}{(x^2 y^{-3}z^2)(-x^3 y^2 z^3)} } \\\\\\ \large { = (-\dfrac{2}{3}) \dfrac{x^{2+2+2}y^{1+3+5}z^{3+1}}{x^{2+3} y^{-3+2} z^{2+3} } = - \dfrac{2}{3} \dfrac{x^6 y^9 z^4}{x^5 y z^5} = - \dfrac{2}{3} \; \dfrac{x y^{10} }{z} }

  15. \large { (4 x^{2/3})(-8x^{1/2}) = (4 \times; (-8))(x^{2/3+1/2}) = - 32 x^{7/6} }

  16. \large { (4 x)^{3/2}(9x)^{1/2} = 4^{3/2} x^{3/2} 9^{1/2} x^{1/2} = (\sqrt 4)^3 (\sqrt 9) x^{3/2+1/2} = 8 \times 3 x^2 = 24 x^2}

  17. \large { (- 27 x^{3/2})^{1/3} = (- 27)^{1/3} (x^{3/2})^{1/3} = \sqrt[3]{-27} x^{3/2 \times 1/3} = - 3 x^{1/2} = - 3 \sqrt x }

  18. \large {\left (\dfrac{-8x^3}{y^{-6}} \right)^{2/3} = \dfrac{(-8x^3)^{2/3}} {(y^{-6})^{2/3}} = \dfrac{(-8)^{2/3} (x^3)^{2/3}} {(y^{-6 \times (2/3)}}} \\\\\\ \large { = \dfrac{(\sqrt[3]{-8})^2 (x^{3 \times (2/3)})} {(y^{-4})} = 4 x^2 y^4 }

  19. \large { x^{5/3} x^{1/6} x ^{-11/6} = x^{5/3+1/6 -11/6} = x^0 = 1 , x \ne 0 }


Question 4


  1. \large { \sqrt{x^2} = | x |}

  2. \large { \sqrt[4]{16x^4} = \sqrt[4]{16} \sqrt[4]{x^4} = 4 | x | }

  3. \large { \sqrt{(2x - 1)^2} = |2x - 1| }

  4. \large { \sqrt[3]{-27x^3} = \sqrt[3]{-27} \sqrt[3]{x^3} = \sqrt[3]{(-3)^3} \sqrt[3]{x^3} = - 3 x }

  5. \large { \sqrt[3]{8 x^6 y^3} = \sqrt[3]{8} \sqrt[3]{ x^6} \sqrt[3]{y^3} = 2 x^{6/3} y = 2 x^2 y}

  6. \large { \sqrt{x^3} \sqrt{x^2} = \sqrt{x^3 x^2} = \sqrt{x^{3+2}} = \sqrt{x^5} = \sqrt{x^4 \times x} = x^2 \sqrt x }

  7. \large { \sqrt[3]{\left (\dfrac{-8x^6}{y^{-3}} \right)} = \dfrac{\sqrt[3]{-8x^6}}{\sqrt[3]{y^{-3}}} = \dfrac{\sqrt[3]{-8} \sqrt[3]{x^6}} {\sqrt[3]{y^{-3} }} }\\\\\\ \large { = \dfrac{\sqrt[3]{(-2)^3} \sqrt[3]{(x^2)^3}} {\sqrt[3]{(y^{-1})^3 }} = \dfrac{-2 x^2}{y^{-1}} = -2 x^2 y}

  8. \large { \dfrac{ \sqrt[5]{64x^9 y^7}}{ \sqrt[5]{2 x^4 y^2}} = \sqrt[5] {\dfrac{64x^9 y^7}{2 x^4 y^2}}} \\\\\\ \large { = \sqrt[5] {32 x^{9-4} y^{7-2}} = \sqrt[5] {2^5} \sqrt[5] x^{5} \sqrt[5] y^{5} = 2 x y }

  9. \large { (4\sqrt[8]{b^2})( 5\sqrt[8]{b^3})( \sqrt[8]{b^3}) = (4 \times 5) \sqrt[8]{b^2 b^3 b^3 } = 20 \sqrt[8]{b^8 } = 20 |b| = 20 b }
    Note: In the last question; since 8√(b3) is real then b is greater than or equal to zero. Hence |b| = b.

More References and links

the rules for radicals and exponents
simplify radical expressions
Divide Radical Expressions
Radical Expressions

Home Page